Analisis dan Sistem Informasi Kartu Nelayan untuk Masyarakat Studi Kasus: Dinas Kelautan dan Perikanan Provinsi Kepulauan Bangka Belitung - Kiswanto . (RJOCS (Riau Journal of Computer Science), 2018)
The Office of Marine and Fisheries of Bangka Belitung Islands Province is the implementing element of the Provincial Government in the field of marine and fisheries which has the main duty according to the Decree of the Governor of Bangka Belitung Islands Number 6 Year 2003 which applies its authority. Decentralization and deconcentration of duties in the field of marine and fisheries. The Office of Marine Affairs and Fisheries is responsible for managing the household affairs and consulting duties of the Islands Province of Bangka Belitung Islands and the specific tasks delegated by the Central Government in the field of Marine and Fisheries. Therefore, the Office of Marine and Fisheries can provide excellent service and distribute fishing cards to the people of Bangka Belitung. One effort that can be done is to improve the card information system of fishermen with computerized and integrated system in order to provide accurate and targeted information.